Determination of Band Gap Energy of ZnO/Au Nanoparticles Resulting in Laser Ablation in Liquid - Julita, Mardiana; Shiddiq, Muhandis; Khair, Miftahul (Indonesian Journal of Chemical Research, 2022)
The synthesis of ZnO and ZnO/Au nanoparticles using the laser ablation method in liquid has been successfully carried out. Characterizing the optical properties of ZnO and ZnO/Au using a UV-Vis Spectrophotometer (Ocean Optic MAYA Pro 2000) measured in the wavelength range of 275-875 nm. The characterization results obtained are absorbance and band gap values of ZnO and ZnO/Au nanoparticles. This study found the absorbance values of ZnO nanoparticles at wavelengths 330 and 335 nm. After obtaining the absorbance value, the band gap value was analyzed for ZnO and ZnO/Au nanoparticles, respectively, 3.23 eV and 3.17 eV. The decrease in the band gap value in ZnO is due to the presence of Au in ZnO nanoparticles which can replace one of the lattices in the ZnO crystal structure.